2018
DOI: 10.1016/j.bpj.2018.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Cooperative Nature of ATP Hydrolysis in Actin Filaments

Abstract: Actin filaments continually assemble and disassemble within a cell. Assembled filaments ''age'' as a bound nucleotide ATP within each actin subunit quickly hydrolyzes followed by a slower release of the phosphate P i , leaving behind a bound ADP. This subtle change in nucleotide state of actin subunits affects filament rigidity as well as its interactions with binding partners. We present here a systematic multiscale ultra-coarse-graining approach that provides a computationally efficient way to simulate a lon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 76 publications
0
39
0
Order By: Relevance
“…The foregoing showed that either depletion or inhibition of Nampt reduced the levels of both NAD and ATP in oocytes. Due to the key role of the actin cytoskeleton in asymmetric division and the importance of ATP and Nampt-dependent NAD for actin regulation [22][23][24] , we therefore investigated whether altered F-actin behaviour might contribute to defective asymmetry following Nampt-depletion. Cytoplasmic F-actin polymerisation undergoes a marked increase at the time of anaphase-onset in oocytes detectable using a fluorescent utrophin probe (UtrCH-mCherry) 2,7,25,26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The foregoing showed that either depletion or inhibition of Nampt reduced the levels of both NAD and ATP in oocytes. Due to the key role of the actin cytoskeleton in asymmetric division and the importance of ATP and Nampt-dependent NAD for actin regulation [22][23][24] , we therefore investigated whether altered F-actin behaviour might contribute to defective asymmetry following Nampt-depletion. Cytoplasmic F-actin polymerisation undergoes a marked increase at the time of anaphase-onset in oocytes detectable using a fluorescent utrophin probe (UtrCH-mCherry) 2,7,25,26 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, disruption of kinesin family members including Kif4 41 , HSET (a kinesin-14) 42 and Kif17 43 increase spindle length and in the case of Kif4 44 and Kif17 43 , lead to enlarged first PBs. The actin cytoskeleton, which mediates spindle movement in oocytes 1,7 , is also heavily dependent upon ATP availability [22][23][24]45 . However, our work did not identify any alterations in either cortical or cytoplasmic F-actin behaviour following Nampt-depletion, although it remains possible that another actin-dependent process may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…The proteolytic cleavage of the spike and large-scaleconformational shift towards fusion peptide insertion, however, are more difficult to sample in atomistic simulations. To address these issues, one can use CG molecular simulation techniques that allow CG particles to adaptively switch discrete "states" and interactions, such as "Ultra-Coarse-Graining" (UCG)(57)(58)(59). In the limit of infrequent internal state switches, UCG implements microscopically reversible state changes are coupled to a Metropolis Hastings like criterion:…”
mentioning
confidence: 99%
“…Such models reduce large-scale complex process into simpler phenomenology, but typically have somewhat limited predictive power and can potentially lack a rigorous justification for the choice of parameters involved. On the other hand, Bbottom-up^CG models of actin filaments with a CG force-field parameterized using reference AA simulations, such as the hetero-elastic network model (hENM), have been found to be adequate in studying actin filaments in terms of their structure and mechanical properties (Chu and Voth 2005;Chu and Voth 2006;Deriu et al 2011;Katkar et al 2018;Lyman et al 2008;Saunders and Voth 2012b;Schramm et al 2017;Voth 2017;Zhang et al 2008). We limit this review below to such bottom-up CG models.…”
Section: Coarse-grained Modeling Of Actinmentioning
confidence: 99%
“…d Intuitive 12-sitesper-subunit CG model of actin, shown in a subunit and a section of the filament. e Cooperativity in phosphate release rate (reproduced from Katkar et al (2018)) et Fan et al 2012;Hocky et al 2016;Lyman et al 2008;Pfaendtner et al 2010a;Pfaendtner et al 2010b;Pfaendtner et al 2012;Saunders and Voth 2012a;Saunders and Voth 2012b;Schramm et al 2017;Yogurtcu et al 2012) and properties of the single subunit (Chu and Voth 2005;Mehrafrooz and Shamloo 2018;Pfaendtner et al 2009;Saunders et al 2014;Saunders and Voth 2011) to the hydrolysis of the bound nucleotide (Akola and Jones 2006;Freedman et al 2012;McCullagh et al 2014;Sun et al 2017). At the highest resolution, ab initio molecular dynamics (AIMD), density functional theory, or quantum mechanics/ molecular mechanics (QM/MM) simulations allow one to simulate the reactive nature of chemical bonds in ATP and surrounding species using electronic structure theory and the rest of the system using molecular mechanics to make the simulations computationally more efficient.…”
Section: Introductionmentioning
confidence: 99%